RNA-dependent oligomerization of APOBEC3G is required for restriction of HIV-1. - Hendrik Huthoff; Flavia Autore; Sarah Gallois-Montbrun; Franca Fraternali; Michael H Malim (PLoS Pathogens)
The human cytidine deaminase APOBEC3G (A3G) is a potent inhibitor of retroviruses and transposable elements and is able to deaminate cytidines to uridines in single-stranded DNA replication intermediates. A3G contains two canonical cytidine deaminase domains (CDAs), of which only the C-terminal one is known to mediate cytidine deamination. By exploiting the crystal structure of the related tetrameric APOBEC2 (A2) protein, we identified residues within A3G that have the potential to mediate oligomerization of the protein. Using yeast two-hybrid assays, co-immunoprecipitation, and chemical crosslinking, we show that tyrosine-124 and tryptophan-127 within the enzymatically inactive N-terminal CDA domain mediate A3G oligomerization, and this coincides with packaging into HIV-1 virions. In addition to the importance of specific residues in A3G, oligomerization is also shown to be RNA-dependent. Homology modelling of A3G onto the A2 template structure indicates an accumulation of positive charge in a pocket formed by a putative dimer interface. Substitution of arginine residues at positions 24, 30, and 136 within this pocket resulted in reduced virus inhibition, virion packaging, and oligomerization. Consistent with RNA serving a central role in all these activities, the oligomerization-deficient A3G proteins associated less efficiently with several cellular RNA molecules. Accordingly, we propose that occupation of the positively charged pocket by RNA promotes A3G oligomerization, packaging into virions and antiviral function.